Astragalus polysaccharide enhances maternal mucosal immunity against PEDV - Jianli Tang; Shuaiyong Wang; Jianmei Tang; Jinming Li (mSphere)
ABSTRACT Porcine epidemic diarrhea virus (PEDV), the major causative pathogen of porcine epidemic diarrhea, poses a severe threat to the swine industry, particularly affecting neonatal piglets. Maternal milk-derived IgA antibody is crucial for protecting piglets from PEDV infection. Despite the effectiveness of current intramuscularly administered PEDV vaccines in inducing strong systemic immune responses, their ability to generate high levels of maternal milk IgA is limited. This study explores the potential of Astragalus polysaccharide (APS) to enhance PEDV vaccine efficacy, specifically focusing on maternal milk IgA levels. We first evaluated anti-PEDV antibody levels in the blood and colostrum of sows vaccinated with PEDV or subjected to feedback feeding. Our results indicated that while vaccination induced robust serum PEDV-specific IgG and IgA, milk IgA levels were lower compared to the feedback group. To address this limitation, APS was administered orally to sows before PEDV vaccination. APS supplementation significantly increased both serum and milk PEDV-specific IgA levels and enhanced cellular immune responses, as evidenced by elevated cytokine levels. Further analysis demonstrated that APS improved intestinal immune function and homeostasis in piglets. Overall, APS supplementation proved to be an effective immune booster, enhancing PEDV vaccine-induced mucosal immunity and providing a promising strategy for improving maternal immunity and piglet protection against PEDV.IMPORTANCEThis study highlights the limitations of current porcine epidemic diarrhea virus (PEDV) vaccines in inducing sufficient maternal milk IgA, which is crucial for protecting neonatal piglets. By supplementing Astragalus polysaccharide (APS) into the vaccination regimen, we demonstrated a significant enhancement in milk PEDV-specific IgA levels, as well as improved cellular immune responses. APS also bolstered intestinal immune function and homeostasis in piglets. These findings suggest that APS supplementation could serve as an immune booster to enhance maternal immunity, offering a promising approach to better protect piglets against PEDV.